The Media's ObamaCare Dodge. - FERGUSON, ANDREW (Commentary, 2014)
The articles discusses the alleged lack of press oversight regarding the U.S. Patient Protection & Affordable Care Act, also known as "Obamacare." The article examines the purported failure of the press to report on shortcomings on the medical care plan, a column in the periodical "Columbia Journalism Review" that blamed Republicans for any lack in press oversight, and the reaction to former governor of Alaska Sarah Palin's argument that the plan would lead to the creation of death panels.